What modern monetary theory is, and what it is not - Emilio Carnevali; Giuseppe Fontana (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
Modern monetary theory (MMT) has grown in popularity in recent years. Several central bankers have made passing comments about it. However, the publication of two papers by Drumetz/Pfister of the Banque de France in 2021 represents the first attempt at a more systematic assessment of MMT by two scholars with knowledge of and experience in central banking. This is a welcome event in the economic debate. The present paper analyses the merits of Drumetz/Pfister's criticism, and investigates some of the most common sources of "misinterpretation" of MMT.
Keywords: E31; E52; E58; E62; B52; 330; modern monetary theory; government debt; central banking; inflation; fiscal policy